Felietonowość „Szkła Kontaktowego” - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Analysis is dedicated to popular TV program “The Contactlense”. This program has nearlythe biggest popularity among the watchers of TVN24 (the opinion-setting TV Station) andconstitutes curious and original form of TV magazine. Author analyses its generic determinantsand makes an attempt to put a generic diagnosis – which genre is nearest to “Contactlense” andwhich characters allow to say about its feuilletonic aspect. Text includes also observation about allthe interactive elements and its generic role. Furthermore, “Contactlense” is seen as a trendsetteramongst TV magazines and could be interesting discussion subject.